The effects of neurofeedback on Event Related Potential (ERP) in zikr meditation - Helman, Nur Arina Ayuni (2020)
The study of human brain activity using electroencephalogram (EEG) is a growing multidisciplinary field that links electronics, psychology and cognitive science to learn the effect of human brainwave activities in various fields e.g. meditation. In this research, an experiment is performed to compare the EEG-Alpha rhythm between Zikr meditation and listening relaxing music. The hardware use is the EMOTIV EPOCH Neuroheadset of 16 electrode channels. The investigation are focused on the Electroencephalography (EEG) signal for exploring the relativity of attentional control by observing Topographic Map through Event Related Potential (ERP) analysis to see whether the brain experience any changes. Then, Power Spectrum Density (PSD) through Auditory Evoked Potential (AEP) analysis is recorded to see the different in each of brain lobes. The effect of the EEG spectral analysis on neurofeedback relaxation technique is also been observed. The results were observed from the frontal lobe and the average alpha power in the region is obtained. Comparison of the experiments works were carried out to observe the relaxation states of the subject while listening to Zikr and the relaxing music. Results from 5 subjects shows that 90% of the subjects’ alpha wave was dominant to Zikr. From the result, 4 out of 5 students tend to have better relaxation when listening to Zikr thus proving that the participants are much more relax after listening the Zikr.